Immunomodulation Therapy to Treat Severe Malaria With Multiple Organ Failure - Saige Camara; Amy Buck; Mikayla Burrell; H. David Humes; Stuart L. Goldstein; Carlie N. Myers; Michael Humes (Critical Care Explorations, 2026)
BACKGROUND: Malaria causes more than 600,000 deaths annually. Severe malaria is frequently complicated by acute kidney injury (AKI) and multiple organ failure driven by dysregulated host hyperinflammation. Elevated cytokines, including interleukin-6 and tumor necrosis factor alpha, are associated with disease severity and mortality, yet effective adjunctive immunomodulatory therapies are lacking. We report the first clinical use of the selective cytopheretic device (SCD), an extracorporeal immunomodulatory therapy, in severe malaria. CASE SUMMARY: A 5-year-old girl returning from the Democratic Republic of the Congo presented with fever, shock, 10.9% parasitemia, AKI, and evolving multiple organ dysfunction. Despite IV artesunate and RBC exchange, she developed refractory shock and severe lactic acidosis. Continuous renal replacement therapy with adjunctive SCD therapy was initiated, after which inflammatory markers, vasopressor requirements, and metabolic acidosis improved with progressive organ recovery. CONCLUSIONS: Targeted extracorporeal immunomodulation may represent a promising adjunctive strategy for severe malaria.